Conceptual Model of Inhibiting Factors to Intent as Waste Cooking Oil Collection Facility - Siti Mahsanah Budijati; Fatma Hermining Astuti; Wandhansari Sekar Jatiningrum (OPSI, 2023)
One of the critical points in realizing reverse logistics (RL) activities is determining the collection location for the products to be managed. Used cooking oil is a consumable product that can be collected through RL activities. Currently, the collection of used cooking oil in some food service businesses in the city of Yogyakarta is carried out by collectors. Collectors carry out their activities based on economic interests. In contrast, from the view of long-term interests, the management of used cooking oil is a manifestation of a sustainable supply chain. So that the management of used cooking oil is not solely aimed at economic interests but also to realize environmental sustainability and social support, cooperation between food service businesses is needed. One form of such cooperation is the provision of collection facilities. However, preliminary studies in this research found that no food service businesses were willing to act as collection facilities. For this reason, this study proposes a conceptual model of the inhibiting factors for intending as a used cooking oil collection facility for food service business actors. The research method was carried out through a literature review as the basis for preparing the conceptual model. The resulting model can be used as a basis for further research.